Tell Ahmar III. Neo-Assyrian pottery from area C - Jamieson, Andrew (Ancient Near Eastern studies / Supplement, 2012)
Tell Ahmar, ancient Til Barsib, on the east bank of the Euphrates River, close to the confluence of the Sajur River, was ideally placed to function as a crossing point from upper Mesopotamia to northern Syria. To a large extent the prominent and strategic location of Tell Ahmar determined the Assyrian interest in the site and its apparent that Tell Ahmar reached its maximum size under the Assyrians. This study presents the Neo-Assyrian pottery from the excavations in Area C at Tell Ahmar. At least three buildings were identified in Area C. The distribution of the different pottery wares and types reflects patterns associated with the different activity areas identified within the buildings in Area C. Some wares and types were found with high degrees of frequency, other wares and types occurred infrequently